2011
DOI: 10.1063/1.3583668
|View full text |Cite
|
Sign up to set email alerts
|

Lattice thermal conductivity of a silicon nanowire under surface stress

Abstract: Lattice thermal conductivity in a silicon nanowire with square cross section J. Appl. Phys. 100, 014305 (2006) The effects of surface stress on the lattice thermal conductivity are investigated for a silicon nanowire. A phonon dispersion relation is derived based on a continuum approach for a nanowire under surface stress. The phonon Boltzmann equation and the relaxation time are employed to calculate the lattice thermal conductivity. Surface stress, which has a significant influence on the phonon dispersion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…11 Different methods of reducing the thermal conductivity of SiNWs have been proposed. [12][13][14][15][16][17][18][19] Thin SiNWs with diameters comparable to the dominant phonon wavelength at low temperatures were shown to have low thermal conductivity. 9 While this result is promising, further decrease in the diameter runs into a substantial barrier, due to limitations of fabrication techniques and measurements quantifying the properties of thin nanowires.…”
mentioning
confidence: 99%
“…11 Different methods of reducing the thermal conductivity of SiNWs have been proposed. [12][13][14][15][16][17][18][19] Thin SiNWs with diameters comparable to the dominant phonon wavelength at low temperatures were shown to have low thermal conductivity. 9 While this result is promising, further decrease in the diameter runs into a substantial barrier, due to limitations of fabrication techniques and measurements quantifying the properties of thin nanowires.…”
mentioning
confidence: 99%
“…Using the phononic dispersion, the density of states (DOS) and the ballistic transmission (number of modes at given energy) are calculated as shown in Ref. [16] by: i q i i i q DOS DOS (6) and…”
mentioning
confidence: 99%
“…Numerous studies can be found in the literature regarding the thermal conductivity of Si NWs [3,4,5,6,7]. The effects of different scattering mechanisms, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The fixed structures of solids can also be tuned by applying mechanical stress. 1,2 Since incompressible fluids are generally homogeneous, these have been typically ignored for such use. Often it is important to be able to tune such devices for specific applications.…”
mentioning
confidence: 99%